Pemanfaatan e-book digital untuk meningkatkan keterampilan menulis dongeng pada Siswa Sekolah Dasar - Utari, Risma; Iswara, Prana Dwija; Aeni, Ani Nur (Academy of Education Journal, 2024)
This research aims to find out how interested in learning, as well as improving the skills of writing fairy tales in class III students at SDN Mandalaherang III by utilizing a learning media in the form of digital e-books based on Flip Book. The number of subjects who took part in this research was 32 people, consisting of class III students, 1 homeroom teacher, and 1 media expert. The data collection method that researchers used this time was observation or interviews with the homeroom teacher, and also written tests for students. Based on the research results that have been obtained, it can be concluded that the average score produced by students is 85 with a greater percentage of aspects of suitability of the storyline with consecutive images, meaning that the use of Flip Book-based digital media can help students improve their writing skills. especially in writing fairy tales in Indonesian subjects.